Streamlining norms: a renewed approach for Finance Commission - Chalam, K.S.R.V.S.; Mishra, Rajiv (1997)
The mechanism of vertical and horizontal transfers of financial resources from the centre to states and among different states, particularly under the aegis of the Finance Commission is characterised by varying degrees of complexity. Though a complex mechanism theoretically purports to justify a greater representation of justifiable needs of both centre and states, in praxis, the devolution mechanism does not guarantee the fulfilment of desired ends. If the pursuit of desired ends through complexity borders on futility, then a more simple mechanism cannot do worse. This paper attempts to highlight the virtues of a simple mechanism that is broadly targeted at the aspirations of the federal constituents of our polity. It further seeks to contribute to the debate on fiscal management and argues for its incorporation as one of the criteria in the devolution schemes. - Reproduced
Keywords: Public finance